Quality and Purchase Intention Percieved Towards low Cost Energy- Saving Cars - Edhie Budi Setiawan (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2015)
Low cost car does not mean having low quality. This is the assumption that the producers or sellers of especially energy-saving car want to push away. This research on the desire and expectation of every car producer and dealer in Indonesia who try to be perceived as having the best quality in the eyes of their consumers and on the increase of consumer buying intention is carried out using a qualitative method as well as the concept of perceived service quality—which shows the difference between bibliographic study and the actual condition.